Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the quadratic equation [tex]\( x^2 + 2x + 1 = 0 \)[/tex] using the quadratic formula, let's follow these steps carefully:
1. Identify the coefficients:
The quadratic equation is given in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex]. By comparing, we can identify:
[tex]\[ a = 1 \quad \text{(coefficient of \(x^2\))} \\ b = 2 \quad \text{(coefficient of \(x\))} \\ c = 1 \quad \text{(constant term)} \][/tex]
2. Write the quadratic formula:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Calculate the discriminant:
The discriminant is given by [tex]\( b^2 - 4ac \)[/tex]. Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 2^2 - 4 \cdot 1 \cdot 1 = 4 - 4 = 0 \][/tex]
4. Substitute the values into the quadratic formula:
Since the discriminant is 0, we will have one real solution (a repeated root):
[tex]\[ x = \frac{-b \pm \sqrt{0}}{2a} = \frac{-2 \pm 0}{2 \cdot 1} = \frac{-2}{2} = -1 \][/tex]
Thus, the solution to the quadratic equation [tex]\( x^2 + 2x + 1 = 0 \)[/tex] is:
[tex]\[ x = -1 \][/tex]
This is a repeated root, meaning the quadratic equation has a double root at [tex]\( x = -1 \)[/tex].
So the answer is:
[tex]\[ x = -1 \][/tex]
1. Identify the coefficients:
The quadratic equation is given in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex]. By comparing, we can identify:
[tex]\[ a = 1 \quad \text{(coefficient of \(x^2\))} \\ b = 2 \quad \text{(coefficient of \(x\))} \\ c = 1 \quad \text{(constant term)} \][/tex]
2. Write the quadratic formula:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Calculate the discriminant:
The discriminant is given by [tex]\( b^2 - 4ac \)[/tex]. Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 2^2 - 4 \cdot 1 \cdot 1 = 4 - 4 = 0 \][/tex]
4. Substitute the values into the quadratic formula:
Since the discriminant is 0, we will have one real solution (a repeated root):
[tex]\[ x = \frac{-b \pm \sqrt{0}}{2a} = \frac{-2 \pm 0}{2 \cdot 1} = \frac{-2}{2} = -1 \][/tex]
Thus, the solution to the quadratic equation [tex]\( x^2 + 2x + 1 = 0 \)[/tex] is:
[tex]\[ x = -1 \][/tex]
This is a repeated root, meaning the quadratic equation has a double root at [tex]\( x = -1 \)[/tex].
So the answer is:
[tex]\[ x = -1 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.